Strategic autonomy of Russia in the changing international environment and consequences for the regional security of the Balkans - Proroković Dušan (Srpska Politička Misao)
Changes in the character and intensity of international relations also cause changes in the strategic approaches of key actors. The current and future actions are projected in accordance with the newly created circumstances, as a result of which the previous doctrines are changed. In this context, this paper analyzes the change in Russia's approach after February 2022, which is reflected in both domestic and foreign policy. Russia's goal is to ensure strategic autonomy in relation to the collective West, which implies applying the concept of extended deterrence instead of insisting on nuclear deterrence. Despite the fact that there are still many doubts about the implementation of the idea of ensuring strategic deterrence, the very establishment of this approach hints at major and comprehensive changes that must be considered. The aim of the research is to analyze the realization of Russia's strategic autonomy by applying the concept of extended deterrence for the regional security of the Balkans. For this, the methods of discourse analysis (direction of Russian policy) and content analysis (individual strategic documents and statements of representative officials), case studies (Balkan regional framework) and synthesis are used. The research relied on the theoretical framework of neorealism while considering states as key actors in international relations. The hypothesis being proven is that despite the unpredictability of further events and the vagueness of the great powers' strategies, Russia's turn towards ensuring strategic autonomy will have consequences for the regional security of the Balkans because it will induce a confrontation with NATO in this geographical area, which is important for the application of the concept of extended deterrence.